Laparoscopic treatment of an ovarian teratoma with perforation of the small bowel: A case report - Naho Tokunaga; Sotaro Hayashi; Eriko Iito; Tomohito Kobiyama; Koki Yagi; Mao Sekimata; Naoki Abe; Sachino Kira; Hajime Takeuchi; Lifa Lee; Satoshi Nishiyama; Maki Goto; et al. (Case Reports in Women's Health, 2025)
Fistula formation is a rare complication of ovarian mature cystic teratoma. This article reports a case of an ovarian mature cystic teratoma associated with fistula formation to the small bowel. A 30-year-old woman, gravida 0, presented with a 1-week history of vague lower abdominal pain and fever. Computed tomography revealed a right ovarian tumor with suspected rupture. Magnetic resonance imaging suggested a mature cystic teratoma and a possible right fallopian tube abscess. Empirical intravenous antibiotic therapy led to clinical improvement; however, the patient subsequently reported bloody stool. During laparoscopic surgery, dense adhesions were found between the right ovarian tumor and the small bowel. Dissection revealed a fistula connecting the ovarian mass to the bowel. A segmental small bowel resection and right ovarian cystectomy were performed. Histopathological analysis confirmed an ovarian mature cystic teratoma with associated intestinal inflammation, but no malignancy. This case highlights the rare but serious complication of fistula formation in ovarian mature cystic teratomas. In patients presenting with gastrointestinal symptoms, especially hematochezia, clinicians should consider the possibility of fistulization and involve gastrointestinal surgery teams as appropriate.